(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper contains a general approach to the urbanism of Iberian culture and the importance of his archaeological recuperation in last thirty years. Also the spatial organization in the way of Archaeological Landscape and the particular arrangement of urbanism and architecture in the Iberian settlement like an archaeological laboratory in order to sociological analysis.